Pengetahuan dan Perilaku Seksual Pranikah pada Remaja SMA di Wilayah Kerja Puskesmas Tampaksiring I - Rustiari Dewi, Ni Luh Putu; Wirakusuma, Ida Bagus (E-Jurnal Medika Udayana; Vol 6 No 10 (2017): E-Jurnal Medika Udayana, 2017)
The survey conducted by BKKBN in 2012 resulted in 48,1% 15 to 19 year-old women who were pregnant before marriage which were caused by free sexual behavior. In 2014 women who were pregnant before marriage were conducted 0,4% by Tampaksiring Public Health Centre I. This study has objective to describe the youth level knowledge and premarital sexual behavior among high school teenagers at Tampaksiring Public Health Centre I working place. This research was carried out in a descriptive quantitative cross-sectional study. The samples were grade XII students of SMA Amarawati dan SMK Pariwisata Trisakti with a total sample of 123 persons that attended filling the questionnaires, but 15 persons didn’t fill the whole questionnaires which exclude from the sample. Data was collected using questionnaires. 48,1% of 108 respondents had inadequate knowledge level mainly knowledge about sexual behavior, only 38% of children answered correctly. The number of childen who had a relationship of 90.7% with sexual behavior most was hugging and kissing the cheek of 81% and sexual intercourse were 11 children (10.2%).